(untitled) (The São Paulo Journal of Mathematical Sciences, 2013)
We give an overview of the development of algebras of generalzied funtions in the sense of Colombeau and recent advances concerning diffeomorphism invariant global algebras of generalized funtions and tensor fields. We furthermore provide a survey on possible applications in general relativity in light of the limitations of distribution theory.